Devulcanization of waste rubber powder using thiobisphenols as novel reclaiming agent. (August 2018) - Zhang, Xiaojie; Saha, Prosenjit; Cao, Lan; Li, Huan; Kim, Jinkuk
Highlights: Chemo-thermomechanical devulcanization process of waste rubber powder. 4, 4′-dithiobis(2, 6-di-t-butylphenol) used as a reclaiming agent for the first time. A brief description of devulcanization and revulcanization mechanism. Abstract: In this study, thiobisphenols, 4, 4′-dithiobis(2, 6-di-t-butylphenol), was synthesized and used as novel reclaiming agent for the chemo-thermomechanical devulcanization process of waste rubber powder (WRP). The devulcanization process was carried out in an internal mixer at 180 °C and 200 °C using different content of reclaiming agent such as thiobisphenols. The degree of devulcanization was estimated by measuring sol content, crosslink density, and Mooney viscosity of the reclaimed rubber (RR). Devulcanization conditions have been studied further with respect to the processability, and the mechanical properties of the revulcanized reclaimed rubber (REVR). Photomicrographs from scanning electron microscopy (SEM) indicate the improvement of the coherency in the REVR with increasing degree of devulcanization. Dynamic properties were also studied for REVR. Again, in order to establish the effect of thiobisphenols as reclaiming agent, the devulcanization of WRP and revulcanization of RR were also evaluated in this study.